Patient and System Factors Associated with Racial and Ethnic Disparities in Ambulatory Care Among Medicaid‐Enrolled Adults with Intellectual and Developmental Disabilities - Chakravarty, S. (Health Serv Res, 2020)
RESEARCH OBJECTIVE: Persons with intellectual and developmental disabilities (IDD) have complex medical needs and experience gaps in care due to their unique needs, and challenges faced by health professionals in responding to them. We characterize New Jersey Medicaid‐enrolled individuals with IDD and examine racial and ethnic (RE) disparities in ambulatory care (AC) quality and the extent to which RE gaps are explained by patient and health system factors. We focus on the potential positive effect of home and community‐based services (HCBS) provided through Medicaid waiver programs in mitigating disparities and improving care. STUDY DESIGN: Utilizing New Jersey Medicaid comprehensive claims data over 2011‐2017, quality of AC was assessed using AC sensitive preventable hospitalizations (PH), IDD‐specific PH (IDDPH), and ED visits. Additional metrics including rates of preventive care visits (cancer screening, vaccination) and quality of behavioral health (BH) care will be available by the time of the conference. Econometric modeling of disparities utilized the Institute of Medicine as well as the Residual Direct Effect approaches that adjust for patient characteristics (sex, age, number of chronic and IDD conditions, presence of BH condition), allowing for mediation of disparities through provider and system‐level factors, for example, average quality of AC in zip code of residence. Difference‐in‐difference estimation examined how availability of HCBS waiver services impacted differences in quality across racial/ethnic groups. Findings from analysis utilizing an area‐level instrumental variable addressing potential selection into waiver services and access to IDD‐specialized providers will be available for the conference. Statistical significance was assessed at P = .05 threshold. POPULATION STUDIED: 37 078 Medicaid‐enrolled individuals of age 22+ over 2011‐2017, who reside: a) in DD intermediate care facilities, or b) in the community and receive HCBS from waiver programs, or c) in the community, do not receive Medicaid‐paid HCBS and diagnosed with one or more of 13 IDD conditions. We examined ambulatory care among 92.7% of this population (n = 34 382) who were always in the community. PRINCIPAL FINDINGS: 44.2% of the community population was female, the mean age was 45.5 years, 59.3% had a BH condition, 25.6% had 3+ chronic conditions, and 49.4% were enrolled in HCBS waivers that provide services such as case management, day habilitation, and assistive technology. Among them, black (OR = 0.55) and Hispanic (OR = 0.21) populations had lower adjusted odds of being enrolled in waivers providing HCBS. Among those not receiving Medicaid‐paid HCBS, blacks had higher odds of PH (OR = 1.50), ED visits (OR = 1.33), and IDDPH (OR = 1.11). Hispanics had higher odds of ED visits (OR = 1.12). However, these disparities did not exist for individuals enrolled in HCBS waiver programs. CONCLUSIONS: Our analysis sheds light on RE disparities in AC outcomes within the IDD population using established measures of care quality and identifies several mechanisms associated with such disparities. We found a positive effect of HCBS on these outcomes in mitigating such disparities. IMPLICATIONS FOR POLICY OR PRACTICE: These findings underscore the beneficial role played by state waivers in ensuring provision of HCBS to individuals with IDD and, additionally, may guide formulation of performance metrics within Medicaid managed care contracts, and guidelines for health professionals offering specific IDD and medical services. PRIMARY FUNDING SOURCE: Agency for Healthcare Research and Quality.